New self-checking Booth multipliers - Hunger, Marc; Marienfeld, Daniel (Zielona Góra: Uniwersytet Zielonogórski)
This work presents the first self-checking Booth-3 multiplier and a new self-checking Booth-2 multiplier using parity prediction. We propose a method which combines error-detection of Booth-3 (or Booth-2) decoder cells and parity prediction. Additionally, code disjointness is ensured by reusing logic for partial product generation. Parity prediction is applied to a carry-save-adder with the standard sign-bit extension.
Keywords: Booth multiplier; self-checking; parity-prediction; carry-dependent adder; 1-out-of-5 code